2004
DOI: 10.1023/b:trag.0000026074.11859.77
|View full text |Cite
|
Sign up to set email alerts
|

Bi-directional Duplex Promoters with Duplicated Enhancers Significantly Increase Transgene Expression in Grape and Tobacco

Abstract: Novel bi-directional duplex promoters (BDDP) were constructed by placing two identical core promoters divergently on both upstream and downstream sides of their duplicated enhancer elements. Estimates of promoter function were obtained by creating versions of CaMV 35S and CsVMV BDDPs that contained reporter marker genes encoding beta-glucuronidase (GUS) and enhanced green fluorescent protein (EGFP) interchangeably linked either to the upstream or downstream core promoters. GUS was used for quantitative analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 32 publications
4
48
0
Order By: Relevance
“…This strategy was based on the hypothesis that, for many promoters, only the core promoter sequence needs to be oriented with respect to the coding sequence of the gene to ensure transcription in the correct direction, while the upstream promoter elements can be present in either orientation (Peremarti et al 2010). Previously, several studies also employed the same or a similar strategy to produce chimeric bidirectional promoters from unidirectional ones (Barfield and Pua 1991;Xie et al 2001;Li et al 2004;Chaturvedi et al 2006;Lv et al 2009), which provides precedence for the biotechnological application of this hypothesis.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This strategy was based on the hypothesis that, for many promoters, only the core promoter sequence needs to be oriented with respect to the coding sequence of the gene to ensure transcription in the correct direction, while the upstream promoter elements can be present in either orientation (Peremarti et al 2010). Previously, several studies also employed the same or a similar strategy to produce chimeric bidirectional promoters from unidirectional ones (Barfield and Pua 1991;Xie et al 2001;Li et al 2004;Chaturvedi et al 2006;Lv et al 2009), which provides precedence for the biotechnological application of this hypothesis.…”
Section: Resultsmentioning
confidence: 96%
“…In addition to the inducible activity of the selected promoter, it is also desirable to design a regulatory module that would express multigene traits in a coordinately regulated manner (Halpin 2005). One strategy is to modify a unidirectional promoter into a bidirectional one, as shown by several key studies (Barfield and Pua 1991;Xie et al 2001;Li et al 2004;Chaturvedi et al 2006;Lv et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Xie et al (2001) have demonstrated the essence and utility of an artiWcial bidirectional promoter derived from CaMV35S. Subsequently several researchers developed bidirectional promoters from existing unidirectional promoters or from artiWcially designed synthetic sequences using a similar approach (Frey et al 2001;Li et al 2004;Chaturvedi et al 2006;Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Use of bi-directional promoter would ensure simultaneous expression of two genes and also halve the number of promoters needed for expressing transgenes (Li et al 2004) and thus minimize the amount of foreign DNA in transgenic plants. Further, homology-dependent gene silencing due to the repeated use of a promoter can be avoided through the use of bi-directional promoter.…”
Section: Introductionmentioning
confidence: 99%